The Cancer Rehabilitation Medicine Metrics Consortium: A Path to Enhanced, Multi-Site Outcome Assessment to Enhance Care and Demonstrate Value - Smith, Sean R.; Vargo, Mary; Zucker, David S.; Henderson, Maryanne; Shahpar, Samman; Wisotzky, Eric M.; Custodio, Christian; Basford, Jeffrey; Jay, Gina; Gerber, Lynn; Cheville, Andrea (Frontiers in Oncology, 2021)
Abstract Purpose: A primary objective stated at the Cancer Rehabilitation Symposium at the National Institutes of Health was to improve outcome measurement. The purpose of this project was for the Cancer Rehabilitation Medicine Metrics Consortium (CRMMC) to develop an assessment tool to evaluate function in cancer patients via a data-driven and methodologically sound process. There is no agreed-upon measure of physical and cognitive function for cancer patients, making it difficult to demonstrate the value of rehabilitation interventions. Cancer patients are a particularly challenging population, with many tumor- and treatment-related variables impacting function. Methods: Investigators from nine different cancer rehabilitation programs participated in a modified-Delphi process to delineate necessary aspects of an ideal patient assessment tool, including instrument type, domains evaluated, applicability across a range of patient traits, clinical feasibility, and item response characteristics. This involved numerous meetings, data review, and analysis of items involved in patient assessment. Results: The CRMMC developed a 21-item patient-reported outcome measure based on item response theory. The process by which the short form was developed was documented and provides a framework for other clinicians to follow. Conclusions: This document provides a framework for rehabilitation providers to follow when developing an assessment tool. This process is described in a stepwise fashion for reproducibility even in different, non-cancer populations.